PENGARUH KELAS IBU BALITA TERHADAP PENINGKATAN PENGETAHUAN IBU MERAWAT BALITA ISPA DI RUMAH - Ari Sulistyawati (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2020)
Mother toddler classes are designed to meet the needs of increasing parental knowledge, one of which is caring for sick toddlers. This study aims to determine the effect of the mother's toddler class on increasing the knowledge of mothers caring for children with acute respiratory infections at home. The population of this research is mothers who have children under five in Klenggotan sub-village, Srimulyo village, Piyungan sub-district, Bantul regency, DIY, totaling 122 people. The sampling technique uses purposive sampling method, there are 22 respondents who met the inclusion criteria. Instrument in the form of a questionnaire containing 20 closed questions about the care of children with acute respiratory infections at home. Bivariate analysis used a paired t test to measure the increase in knowledge of mothers caring for children with acute respiratory infections at home. The results showed that the average age of the mother was 30 years, the age of the child was 18 months, and the number of children was 1-2 people. Most of the mother's education is high school and works as a housewife. T test obtained p value = 0.830, meaning that there is no difference between before and after treatment. It was concluded that the class of toddler mothers did not significantly increase the knowledge of mothers caring for children with acute respiratory infections at home. Further researchers are advised to continue this research using other methods that can describe in full how the impact of the class of toddler mothers on increasing the knowledge of participants. Keywords: pneumonie, upper respiratory tract infections, mother toddles class, knowledge